10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
The FDA has recently approved a medical device which determines a glomerular filtration rate assessment at the point-of-care by transdermal detection of the fluorescent tracer agent relmapirazin. Previous in vitro and in vivo studies on this agent yielded negligible safety/toxicology concern resulting in advancement to phase I, II, and III human clinical studies. Now that clinical use is occurring, herein we investigated possible interference this agent may induce with typical clinical diagnostic assays given to incoming and hospitalized patients. The testing methodology followed the CLSI EP07-A3 Interference Testing in Clinical Chemistry guideline for determination of interference. No interference from relmapirazin was detected in the suite of metabolic and cardiac assays evaluated.